Primary care provider attitudes, experiences and practices about cannabidiol (CBD) and barriers to patient-provider communication about CBD use: A qualitative study - Pravesh Sharma; Ashley Holland; Taharat Sheikh; Blake Novy; Tyler Oesterle; Rheanna Platt; Christopher J. Hammond (Elsevier, 2022)
Objectives: Federal hemp legalization and ongoing shifts in US marijuana laws have led to increased population-wide use of cannabidiol (CBD) supplements, often without the knowledge of primary healthcare providers (PCPs). Given the potential risks related to CBD use, especially in vulnerable subgroups, improved communication is warranted. This study aimed to examine PCP attitudes, experiences, and practice behaviors related to CBD and provider-reported barriers to communication with patients about CBD use. Methods: Fourteen PCPs were recruited and participated in semi-structured interviews. Transcripts were digitally analyzed using inductive thematic analysis. Results: Analyses identified that most PCPs had neutral views about CBD use by their patients. The study found that discussions about CBD use were initiated by patients. Most PCPs cited lack of time, discomfort, low-quality evidence, and low prioritization as reasons for not discussing CBD with patients. Conclusion: PCPs rarely screen for or discuss CBD use with their patients and most of them had neutral views about CBD use by their patients. A number of barriers exist to open dialogue about CBD. Innovation: Our study is the first in-depth report on PCP attitudes, experiences, and practice behaviors related to CBD. The findings of our study have the potential to significantly impact future PCP practice behaviors. These results can inform healthcare system policies around screening for CBD use and PCP communication training. In doing so, these efforts may mitigate risk and optimize benefits related to the expanding CBD market.